DOES BLOCKCHAIN BREAK DOWN OR TRANSFORM THE ISLAMIC FINANCIAL SYSTEM? - Cahayani, Ica (Proceeding International Seminar of Islamic Studies, 2023)
This research discusses blockchain in financial technology (Fintech), and whether it has the potential to break down or transform the Islamic financial system. This research aims to explain blockchain in Fintech and understand the challenges it poses to the Islamic financial system. This topic is important to understand how big the development of global Fintech is towards the Islamic financial system. Particularly, it is still being discussed by the world community such as policymakers, practitioners, researchers, and scholars. As it causes a dilemma for the Islamic financial system because there are various opinions regarding haram and halal of it. On several occasions, the blockchain has driven transformations in the Islamic economic and financial system but on the other, it has also been broken down. Our study shows that blockchain deserves further attention and study to unfold whether it is halal or haram according to Islamic finance law. This study will analyze in depth the debate regarding the topic using the concept of financial technology and the principles of Islamic finance. This study uses an integrative reflection method with non-experimental data and uses an unstructured research strategy. The legal framework for Islamic finance is researched and studied to determine if it can accommodate the rapidly evolving Fintech. Keywords: Financial Technology, Blockchain, Islamic Financial System